AGAMA DAN RITUAL SLAMETAN: Deskripsi-Antropologis Keberagamaan Masyarakat Jawa - Kholil, A. (UIN Maliki Malang, 2009)
Substantially, the core of religious belief believes God as being transcendental, sacred, and pure, above everything related to the Almighty. Functionally, the core of religious belief is an effort to handle life problems: existential problems. Religion always leads to goodness physically and spiritually. However, the followers of religion donât always do it. Diversity thought in a religion using charity done by its followers always colors the practice of the social diversity. It might be caused by a misinterpretation to the doctrine or certain vested interests often happened in the political life. In fact, this is the reality happened in the religious life of our society. âReligious ambiguityâ appears in âslametanâ becoming the tradition of our society, especially Javanese. âSlametanâ presents symbolism that needs more explanation to be rightly understood. âSegagolongâ, âmanungsaâ, and âpecel pitikâ are symbolizing for nine orifices, âmanungal ing rasaâ, and an effort to get goodness.